Evaluación de la eficiencia de la acequia de riego Naranjapamba parroquia San Juan de Pózul, cantón Celica, provincia de Loja - Armijos Torres, Dayana Lisbeth (2023)
With the purpose to know the driving efficiency of the Naranjapamba irrigation canal, this research work proposed to carry out a socioeconomic diagnosis, characterize the technical aspects that limit its operation and build a proposal to improve its efficiency. The methodology that was used was supported by the search for secondary information such as PDOT of the San Juan de Pózul parish, Geoportales, guide for description of soil profiles, etc., tests and methods to determine the infiltration rate, reference evapotranspiration, crop evapotranspiration, effective precipitation, water requirements, gauging by the velocity section and volumetric method, which allowed determining the conduction efficiency. The Naranjapamba neighborhood represents 3,07% of the total population of the parish, men (61 %) and women (39 %), the main activity is agriculture, with the cultivation of corn; By-products such as milk and its derivatives are released from livestock, which boosts the family economy. In the study area, two soil profiles were described, profile one has a depth of 1,05 m, with 3 horizons, the first is an Ap with a thickness of 12 cm, with a loamy-clay texture and an apparent density of 1,5 g cm-3, the second horizon is a Bw1,38 cm thick, clayey texture and apparent density of 1,4 g cm-3, the third horizon is a Bw2, 55 cm thick and clay-loam texture; in profile 2 a depth of 1,0 m, the first horizon is an Ap with a thickness of 35 cm, a loamy-clay texture and an apparent density of 1,2 g cm-3, the second is a Bt2 and the third Bt1 horizon with thickness of 25 and 40 cm respectively have a clayey texture. The ditch is divided into 3 pipes, the first is 190,84 m long, the second 87,82 m and the third 66,7 m, and carries a flow rate of 1,88 l s-1, with a current efficiency that oscillates between 10 and 33 %, which means that 90 and 67 % is lost due to infiltrations and external issues of poor livestock management, which is developed by free grazing, which causes the destruction of the ditch, it is also They create puddles causing the water to not follow its path normally. From the analysis of the water quality it is concluded that it is suitable for agricultural use, since its important parameters such as solid substances in suspension, electrical conductivity, sodium, Sodium Absorption Ratio (RAS), calcium, magnesium are within the permissible limits. Keywords: Irrigation ditch, conduction efficiency, socioeconomic, flow and quality evaluation.